PENGGUNAAN MEDIA PEMBELAJARAN E-LIBRARY UNTUK MENINGKATKAN MINAT BELAJAR SISWA KELAS XI D PADA MATA PELAJARAN SEJARAH DI SMA NEGERI 9 PEKANBARU - penadi kurniawan; Hari Darmansyah; Yanti Ernita; Rahmi Yulia Nurjarwati; Feni Eka Sulistiarini; Isjoni; Altalariq Riza Pratama (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
History learning in schools often faces the challenge of low student interest due to the perception that the subject matter is monotonous. This issue is consistent with initial observations at SMAN 9 Pekanbaru, which revealed low student engagement during the learning process, minimal attention, and limited student participation. The use of information technology can serve as a potential solution, one of which is through the development of an e-library as a digital learning medium. This study aims to examine the effectiveness of an e-library in increasing students' interest in learning history at SMAN 9 Pekanbaru. The research employed a one-group pretest-posttest design, involving a sample of 39 students. The instrument used was a learning interest questionnaire administered before and after students used the elibrary. The findings indicate an increase in students' interest in learning from the pre-cycle to Cycle II. In the pre-cycle, the average percentage of learning interest was at a low level (40% high interest). Following the e-library intervention in Cycle I, the percentage of interest indicators rose to 55%, and further increased to 70% in Cycle II. These findings suggest that the use of the e-library is effective in fostering students' interest in learning history, aligning with previous studies that emphasize digital libraries as valuable tools to enhance access to learning materials and significantly improve students’ reading interest.